Effect of clonidine and gabapentin as oral premedication on hemodynamic response to laryngoscopy and tracheal intubation - Mishra, Prabhati R.; Padhy, Manmaya; Satapathy, Rusikesh; Kar, Monali (International Journal of Research in Medical Sciences, 2018)
Background: Laryngoscopy and endotracheal intubation causes stimulation of symphatho-adrenal system resulting in increase in blood pressure and heart rate. The present study compared oral clonidine, gabapentin and placebo premedication in attenuating haemodynamic response to laryngoscopy and endotracheal intubation. Methods: About 90 adult patients of ASA grade I and II patients in age group of 18-60 yrs, of either sex posted for surgery under general anaesthesia were randomly divided into three groups (30 patients in each group). The study drugs were given orally 90minutes before induction. Group 1 and Group 2 were pre treated with oral clonidine (0.2mg) and gabapentin (800mg) respectively and Group-3 received placebo. The HR, systolic blood pressure, diastolic blood pressure and mean arterial blood pressure were recorded before induction of anesthesia and 1, 3, 5, 10min after laryngoscopy and intubation. Results: It was found that both clonidine and gabapentin reduces HR, SBP, DBP, MAP than placebo group at lminute, 3minutes, 5minutes and 10minutes after intubation. But reduction is more with clonidine as compared to gabapentine and difference was statistically significant (P = <0.0001). Conclusions: Both oral clonidine and gabapentine attenuate hemodynamic response to laryngoscopy and endotracheal intubation but effect is better with clonidine than oral gabapentine.